Book Notes [35, Spring 1995] - Palmer, Bryan D. (Labour/Le Travail, 1995)
The article briefly reviews "Canada and the United States," edited by John Herd Thompson and Stephen J. Randall," "O'Callaghan: The Making and Unmaking of a Rebel," by Jack Verney, "'We're Rooted Here and They Can't Pull Us Up': Essays in African Canadian Women's History," by Peggy Bristow et al., "Crime and Criminal Justice: Essays in the History of Canadian Law," edited by Jim Phillips, Tina Loo, and Susan Lewthwaite, "Matters of the Mind: The University in Ontario, 1791-1951," by A.B. McKillop, "R.C.M.P. Security Bulletins: The Early Years, 1919-1929," edited by Gregory S. Kealey and Reginald Whitaker, "Ethnic Cultures in the 1920s in North America," by Wolfgang Binder, "The 'Lower Sort': Philadelphia's Laboring People, 1750-1800," by Billy G. Smith, "Transforming Rural Life: Dairying Families and Agricultural Change, 1820-1885," by Sally McMurry, "Labor's Struggles, 1945-1950," by Irving Richter, "Participant Observer: An Autobiography," by William Foote Whyte, "Newcomers in the Workplace: Immigrants and the Restructuring of the U.S. Economy," edited by Louise Lampbere, Alex Stepick, and Guillermo Grenier, "Restoring the Promise of American Labor Law," edited by Sheldon Friedman, et al., "The Life and Literary Pursuits of Allen Davenport with a further selection of the author's work," edited by Malcolm Chase, "UK Labour Market: Comparative aspects and institutional Developments," edited by Ray Barrell, "Social Structures of Accumulation: The Political Economy of Growth and Crisis," edited by David M. Kotz, Terrence McDonough, and Michael Reich, "Women, Work, and Place," edited by Audrey Kobayashi, "Color, Class and Country: Experiences of Gender," edited by Gay Young and Bette J. Dickerson, "Making Labour Law in Australia: Industrial Relations, Politics, and Law," by Laura Bennett, and "Making Workers Soviet: Power, Class and Identity," edited by Lewis H. Siegelbaum and Ronald Gregor Suny.